Metabolic Regulation of Cytoplasmic DNA Synthesis - Byrnes, John J. (1974)
The regulation of cytoplasmic DNA synthesis by the metabolites ATP and citrate has been demonstrated. Other ribonucleoside and deoxyribonucleoside triphosphates as well as α,β-methylene- and β,γ-methylene-ATP and α,β-methylene-ADP are able to partially substitute for ATP in stimulating the rate of DNA synthesis with the cytoplasmic DNA polymerase (DNA nucleotidyltransferase, EC 2.7.7.7) from bone marrow. The fact that the methylene analogs of ATP and ADP are effective in stimulating DNA synthesis indicates that the mechanism of stimulation does not involve ATP hydrolysis. The nucleotide activators have been shown by kinetic analysis to affect the V(max) of the enzyme and not the apparent K(m)s for the substrates. The curve that results when the rate of DNA synthesis is plotted as a function of ATP concentration is sigmoidal, suggesting that more than one site on the enzyme interacts with ATP and that these sites are acting cooperatively. The concentration of ATP required for maximal velocity is dependent on the Mn(++) concentration. At pH 7.0 maximal activity is obtained when the molar ratio of ATP to Mn(++) is 1.6:1. When either ATP or Mn(++) is present in relative excess, DNA synthesis is inhibited. The mechanism of ATP activation has been shown to be associated with an alteration in the sedimentation behavior of the DNA polymerase. In the presence of ATP, there is an increase in the fraction of the enzyme that sediments at 8 S with a corresponding decrease in the 11.6S enzyme fraction. Thus, ATP activation corresponds to the dissociation of an 11.6S dimer into 8S monomers. In addition to ATP and other nucleotides, citrate also stimulates DNA synthesis. At present it is not clear whether the stimulatory effects of ATP and citrate are due to their ability to chelate Mn(++), which is inhibitory at high concentrations, or whether an ATP-Mn(++) or citrate-Mn(++) complex is the activator.